KOLABORASI MAHASISWA PPG PRAJABATAN UM DAN SMP NEGERI 25 MALANG DALAM PENGOLAHAN SAMPAH PLASTIK MELALUI PROGRAM ECOBRICK GOES TO SCHOOL - Yani, Ni Luh Sinta; Insani, Nailul; Zakaria, Muhammad Sya’roni; Sulistia, Nita; Aprillaili, Rara Vellanieka; Anggraini, Rima Trisna; Amalinda, Rizkyta; Hartono, Selamat Budi; Noviandari, Tika; Anas, Zaki Nur (Jurnal Abdimas Bina Bangsa, 2024)
The "Ecobrick Goes to School" program is a collaborative initiative between the Pre-service Teacher Professional Education (PPG) students of Universitas Negeri Malang (UM) and SMP Negeri 25 Malang. This program aims to educate students on the importance of plastic waste management through the creation of ecobricks, a simple technology that transforms plastic waste into environmentally friendly building materials. In support of the Adiwiyata School vision, the program is designed to raise students' environmental awareness and promote sustainable practices within the school environment. Through a participatory approach, the PPG students from UM collaborated with teachers and students to conduct a series of educational activities, including ecobrick-making workshops, discussions on the environmental impacts of plastic waste, and the introduction of recycling concepts. The results of this program showed an increase in students' understanding and involvement in waste management efforts, as well as a tangible contribution to reducing plastic waste in the school environment. This collaboration not only provided educational benefits to students but also strengthened the leadership competencies of PPG students in implementing community-based programs. The success of this program highlights the importance of synergy between educational institutions and school communities in addressing global environmental issues through concrete local actions